Construction and Analysis of Cutting Force and Stability Prediction Model in CNC Milling Thin-Walled Parts Machining - Li, Bo; Guo, Chengcao (Transactions on Engineering and Technology Research, 2024)
Thin-walled parts are widely used in precision instruments, automobiles and other fields for their high strength, light weight and other characteristics. However, in the process of CNC milling, as the thickness of the parts decreases, their rigidity gradually decreases, resulting in the machining process is very easy to produce vibration, and even chatter, which seriously affects the accuracy and surface quality of the parts. Traditional manufacturing methods usually use conservative cutting dosage to reduce vibration, but this greatly limits the performance of CNC machine tools and cutting tools. In order to solve this problem, this paper thoroughly investigates the dynamic characteristics of the cutting process of thin-walled parts, and constructs a cutting force and stability prediction model. Through a combination of theoretical analysis, experimental verification and numerical simulation, this paper comprehensively analyses the impact of cutting parameters, tool geometry, workpiece material properties and other factors on cutting force and machining stability. The research results not only help to improve the cutting theory of thin-walled parts, but also provide an important technical support for the realisation of high-efficiency and high-precision machining. The results of this paper show that by optimising the cutting parameters and tool geometry, the cutting force can be effectively reduced and the machining stability can be improved, so as to achieve efficient and high-precision machining of thin-walled parts. In addition, this paper also explores the causes and mechanisms of vibration in the machining process, providing a theoretical basis for the development of targeted vibration control measures. The research in this paper is important for promoting the development of thin-walled parts machining technology, not only helps to improve the processing efficiency and quality of parts, but also helps to promote the manufacturing industry to a more efficient, more precise direction.